Cytisine compared to combination nicotine replacement therapy to reduce cigarette consumption in relapsed smokers: protocol for a pilot randomized controlled trial - Hassan Mir; Javad Heshmati; Kerri-Anne Mullen; Ashley Baldwin; Evyanne Quirouette; Andrew Pipe; Robert Reid (Pilot and Feasibility Studies)
Abstract Background Cigarette smoking is a leading cause of death and disease, including those related to the cardiovascular system. Cytisine is a plant-based medication, which works in a similar mechanism to varenicline. It is safe, efficacious, and cost-effective for smoking cessation. While there are effective therapies such as nicotine replacement therapy, bupropion, varenicline, and cytisine for smoking cessation, relapse remains common. It is unclear how best to support these individuals. This study aims to assess the feasibility of randomizing patients who relapse to combination NRT or cytisine after admission to a cardiac hospital. Study design Randomized, two-group parallel feasibility trial. Methods This trial will recruit relapsed smokers from the University of Ottawa Heart Institute. Participants will be randomized 1:1 to receive cytisine or combination NRT, alongside counseling and follow-up support. Feasibility outcomes include recruitment rates and treatment completion. Secondary outcomes include smoking cessation rates and adverse events. A total of 60 participants will be recruited using stratified randomization by sex to ensure gender balance. Data will be analyzed descriptively, focusing on feasibility and efficacy measures to inform future trials. Discussion The primary aim of this study is to evaluate the feasibility of recruiting patients who were recently admitted to the hospital and have relapsed to smoking within 180 days post-discharge. This will inform future studies aimed at recruiting patients who have relapsed to understand how best to support them to quit smoking. This study will also compare the acceptability, efficacy, and safety of cytisine compared to combination NRT, as demonstrated in previous studies in other populations. Notably, cytisine’s shorter regimen and natural composition broaden its appeal, potentially supporting a wider spectrum of people who smoke. The study’s robust design, infrastructure, and expertise enhance its feasibility. Future research avenues, especially among cardiac patients and relapsed individuals, promise further insights, potentially transforming cessation strategies worldwide. Trial registration Registered at Clinicaltrials.gov (CT04286295) on 14 March 2022. https://clinicaltrials.gov/study/NCT04286295?locStr=Canada&country=Canada&intr=Cytisine&rank=3 .